INTEREST LOAN IN THE PERSPECTIVE OF ISLAMIC JURISPRUDENCE (COMPARATIVE STUDIES) - Daud Rasyid (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractTrading is a fabric of our lives, where lending and borrowing has become a contemporaneous product. What remains constantly changing is the models and means in the transaction. In this day and age, banks issues loans through credit cards to clients for financial transactions with fixed maturity dates and balance limits. Cardholders will be penalized for late payment should the due amount is not settled within the given grace period. Another example in trading activity is when a company seeks public loan funding to cover investment projects. The capital transaction is offered in an exchange of returns in interests and derivatives awarded to participating clients for certain contract durations. These are called interest-based banks. Since the beginning of Islam, Prophet Muhammad, Peace be upon him, prohibited this practice, which at the time was engaged by his uncle, Al-Abbas. Prophet Muhammad, Peace be upon him, firmly said: